Psychosocial correlates of exclusive breastfeeding among mothers in Tuban Regency, Indonesia: a cross-sectional study - Umu Qonitun; Nurus Safa'ah; Miftahul Munir; Ilmiatus Qoyimah; Erna Eka Wijayanti (Pediomaternal Nursing Journal, 2026)
Introduction: Exclusive breastfeeding rates remain suboptimal in Indonesia despite well-documented benefits for infant and maternal health. Multiple psychosocial factors influence a mother's ability to sustain exclusive breastfeeding for six months. Objective: To examine associations between spousal support, healthcare provider support, coping mechanisms, and self-efficacy with exclusive breastfeeding practice among Indonesian mothers. Methods: Using purposive sampling, this cross-sectional study enrolled 150 mothers from Tuban Regency, East Java, with infants aged 0–6 months. Data were collected using validated questionnaires measuring spousal support, healthcare provider support, coping mechanisms, and breastfeeding self-efficacy. Exclusive breastfeeding was defined as providing only breast milk, without any supplemental food or liquid, for a minimum of four months postpartum. Spearman rank correlation (r) tests were used to examine associations between each independent variable and exclusive breastfeeding practice. Results: The majority of participants (72.0%) were aged 26–35 years, held senior high school qualifications (46.0%), and were full-time homemakers (82.0%). Strong-to-very-strong positive correlations were observed for all predictors: healthcare provider support (P-value<.001, r = .923), self-efficacy (P-value<.001, r = .901), spousal support (P-value<.001, r = .847), and coping mechanisms (P-value<.001, r = .634). Conclusion: Spousal support, healthcare provider support, adaptive coping mechanisms, and maternal self-efficacy are each significantly associated with exclusive breastfeeding practice. Interventions targeting these modifiable psychosocial factors—through family education, professional support programs, and maternal empowerment initiatives—may meaningfully improve exclusive breastfeeding rates in similar low-resource settings. Keywords: breastfeeding; health personnel; psychological adaptation; self efficacy; social support